ENGLISH AS A TOOL OF SOFT POWER: THE STRATEGIC ROLE OF LANGUAGE IN INTERNATIONAL RELATIONS - Nigina Ikromova (Bright Mind Publishing, 2025)
Soft power, or the capacity to appeal to and convince through communication, culture, and values, is becoming more and more important in the 21st century for the exercise of global influence. The English language is one of the soft power tools that strategically shapes international relations and diplomacy. This article examines how English, being the universal language, serves as a vehicle for projecting political narratives, values, and influence in addition to being a communication medium. This study critically analyses the empowering and contentious features of English in international politics, drawing on theoretical and practical examples such as language education programs and international institutions.
Keywords: Soft power, English language, diplomacy, public diplomacy, linguistic imperialism, TESOL, international relations.